Key stress factors and parameters for production optimisation of silk-elastin-like proteins in E. coli BL21(DE3) - Collins, Tony (2013)
Silk-elastin-like proteins (SELPs) combining the physicochemical and biological properties of silk and elastin have a high potential for use in the pharmaceutical, regenerative medicine and materials fields. Their development for use is however restrained by their production levels. We have recently synthesised a series of novel silk-elastin-like proteins and here we will describe the optimisation of the production of these with the pET-E. coli BL21(DE3) expression system. Both batch production in shake flasks and fed-batch production approaches were investigated. Furthermore, a comprehensive empirical approach examining all process variables (media, medium composition, inducer, induction time and period, temperature, pH, aeration, agitation, pre- and post-induction growth rates) and a detailed characterisation of the bioprocesses were carried out in an attempt to maximise production and to identify the factors limiting higher production levels. Using the optimised conditions, approximately 0.5 g/l of purified SELP was obtained in shake flasks and as much as 4 g/L was obtained when using the fed-batch approach. These represent, respectively, approximately 10 and almost 100-fold increases on that previously reported for SELPs.